Genome-Based Drug Target Identification in Human Pathogen Streptococcus gallolyticus - Qureshi, Nosheen Afzal; Bakhtiar, Syeda Marriam; Faheem, Muhammad; Shah, Mohibullah; Bari, Ahmed; Mahmood, Hafiz M.; Sohaib, Muhammad; Mothana, Ramzi A.; Ullah, Riaz; Jamal, Syed Babar (Frontiers in Genetics, 2021)
Streptococcus gallolysticus (Sg) is an opportunistic Gram-positive, non-motile bacterium, which causes infective endocarditis, an inflammation of inner lining of heart. As Sg has acquired resistance with the available antibiotics, therefore there is a dire need to find new therapeutic targets and potent drugs to prevent and treat this disease. In the current study, an in silico approach is utilized to link genomic data of Sg species with its proteome to identify putative therapeutic targets. A total of 1,138 core proteins have been identified using pan genomic approach. Further, using subtractive proteomic analysis a set of 18 proteins, essential for bacteria and non-homologous to host (human), were identified. Out of these 18 proteins, 12 cytoplasmic proteins were selected as potential drug targets. These selected proteins were subjected to molecular docking against drug like compounds retrieved from ZINC database. Furthermore, the top docked compounds with lower binding energy were identified. In this work we have identified novel drug and vaccine targets against Sg, of which, some have already been reported and validated in other species. Owning to the experimental validation we believe our methodology and result are significant contribution for drug/vaccine target identification against Sg caused infective endocarditis.